Faculty Perceptions of Online Teaching Effectiveness and Indicators of Quality - Christine Frazer; Debra Henline Sullivan; Deborah Weatherspoon; Leslie Hussey (Nursing Research and Practice)
Online education programs in nursing are increasing rapidly. Faculty need to be competent in their role and possess the skills necessary to positively impact student outcomes. Existing research offers effective teaching strategies for online education; however, there may be some disconnect in the application of these strategies and faculty perceptions of associated outcomes. Focus groups were formed to uncover how nursing faculty in an online program define and describe teaching effectiveness and quality indicators in an asynchronous online environment. A semistructured interview format guided group discussion. Participants (n=11) included nurse educators from an online university with an average of 15 years of experience teaching in nursing academia and 6 years in an online environment. Teaching effectiveness, indicators of quality, and student success were three categories that emerged from the analysis of data. What materialized from the analysis was an overarching concept of a “dance” that occurs in the online environment. Effective online teachers facilitate, connect, lead, and work in synchrony with students to obtain indicators of quality such as student success, student improvement over time, and student application of knowledge to the professional role.